Efficacy of cryotherapy for the treatment of cutaneous leishmaniasis: meta-analyses of clinical trials (2016)
Background: Cryotherapy is a local treatment for cutaneous leishmaniasis with variable efficacy and greater safety than conventional treatment. The objective of this study is to evaluate the efficacy and safety of cryotherapy for the treatment of cutaneous leishmaniasis and to compare it with pentavalent antimonials. Methods: A meta-analysis based on a search of nine databases with eight strategies was conducted. Inclusion and exclusion criteria were applied, the methodological quality of each article was evaluated, and the reproducibility of the study selection and information extraction from each clinical trial was assured. The per lesion and per patient efficacy was calculated, and a meta-analysis of relative risks with the random effects model and the Dersimonian and Laird's, Begg, and Egger tests, along with a sensitivity analysis, were performed. A meta-regression based on the methodological quality of the trials included was also performed. Results: Eight studies were included in which respective per lesion efficacies of 67.3 % and 67.7 % were reported for cryotherapy and pentavalent antimonials. In 271 patients treated with cryotherapy and in 199 with pentavalent antimonials, respective per protocol and intent to treat efficacies of 63.6 % and 54.2 % were found in the first group, and per protocol and intent to treat efficacies of 74.7 % and 68.3 % were found in the second group. The relative risk for the comparison of efficacy in the two groups was 0.73 (0.42–1.29). The results of the sensitivity analysis and the meta-regression analysis of relative risks were statistically equal to the overall results. Conclusion: This investigation provides evidence in favor of the use of cryotherapy given that its efficacy is similar to that of pentavalent antimonials.